2010
DOI: 10.1037/a0021276
|View full text |Cite
|
Sign up to set email alerts
|

New trends in gender and mathematics performance: A meta-analysis.

Abstract: In this paper, we use meta-analysis to analyze gender differences in recent studies of mathematics performance. First, we meta-analyzed data from 242 studies published between 1990 and 2007, representing the testing of 1,286,350 people. Overall, d = .05, indicating no gender difference, and VR = 1.08, indicating nearly equal male and female variances. Second, we analyzed data from large data sets based on probability sampling of U.S. adolescents over the past 20 years: the NLSY, NELS88, LSAY, and NAEP. Effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
500
10
37

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 739 publications
(629 citation statements)
references
References 188 publications
41
500
10
37
Order By: Relevance
“…Generally, the results of empirical research have suggested that men have advantages in mathematical and visuospatial abilities (Linn and Petersen 1985;Voyer et al 1995;Halpern et al 2016), that women have advantages in episodic memory (Halpern et al 2016;Herlitz and Rehnman 2008) and verbal ability (Hyde and Linn 1988;Reilly 2012), and that there are no significant sex differences in category fluency (Crossley et al 1997). Recent studies conducted in more gender-egalitarian societies have found smaller gender differences in levels of mathematical achievement (Guiso et al 2008;Else-Quest et al 2010;Lindberg et al 2010). Gender differences in cognitive tasks have been found to be stable from adulthood to old age, which suggests that age-related declines in cognitive abilities have similar trajectories in men and women (Barnes et al 2003;de Frias et al 2006;Gerstorf et al 2006).…”
Section: Sex Differences In Cognitive Functionmentioning
confidence: 99%
“…Generally, the results of empirical research have suggested that men have advantages in mathematical and visuospatial abilities (Linn and Petersen 1985;Voyer et al 1995;Halpern et al 2016), that women have advantages in episodic memory (Halpern et al 2016;Herlitz and Rehnman 2008) and verbal ability (Hyde and Linn 1988;Reilly 2012), and that there are no significant sex differences in category fluency (Crossley et al 1997). Recent studies conducted in more gender-egalitarian societies have found smaller gender differences in levels of mathematical achievement (Guiso et al 2008;Else-Quest et al 2010;Lindberg et al 2010). Gender differences in cognitive tasks have been found to be stable from adulthood to old age, which suggests that age-related declines in cognitive abilities have similar trajectories in men and women (Barnes et al 2003;de Frias et al 2006;Gerstorf et al 2006).…”
Section: Sex Differences In Cognitive Functionmentioning
confidence: 99%
“…A particular concern is that a larger gap exists at the top end of the distribution. That is, the highest performing boys significantly outperform the highest performing girls (Hedges & Friedman, 1993;Lindberg et al, 2010;Strand, Deary, & Smith, 2006).…”
mentioning
confidence: 99%
“…In a recent meta-analysis, Lindberg et al (2010) concluded that there is no overall gender difference in mathematics performance. However, their data suggest that a small to mediumsized difference exists in high school (d ϭ 0.23) and with high-performing students (d ϭ 0.40).…”
mentioning
confidence: 99%
“…However, such views are not unanimously shared, with other research demonstrating no differences (e.g. Lindberg, Hyde, Linn & Petersen, 2010;Scafidi & Bui, 2010) or, occasionally, stronger numeracy performance in female students (Elmore & Vasu, 1986).…”
Section: Demographicsmentioning
confidence: 83%